Analisis Kepuasan Pelanggan Terhadap Kinerja Pelayanan Yabakii Mart dengan Menggunakan Metode SQ dan QFD - Anisha Dian Iswahyuni; Aji Kusumastuti Hendrawan; Muhammad Miftah Fauzi (Pusat Riset dan Inovasi Nasional, 2022)
YABAKII Mart is a mini market company that offers a variety of daily necessities. During the last three months there have been customers who have complained and are not satisfied with YABAKII Mart's services due to several factors, including inconsistent service, several times of service, and the completeness available. The purpose of this study is to measure customer perceptions of service quality, and provide recommendations for improvements to company services. The method used is Service Quality, and Quality Function Deployment Level 1. In the QFD stage or recommendations for improvement, interviews with the Director of YABAKII Mart. The research was conducted in November-December 2021 by distributing questionnaires to 322 YABAKII Mart customers. Based on the distribution table analysis and the percentage of customer satisfaction obtained 19.25% customers feel very dissatisfied, 23.09% customers feel dissatisfied, 33.19% customers feel quite satisfied, 16.62% customers feel dissatisfied and 7.85 % of customers are very satisfied with YABAKII Mart's services.